Epidemiology of Bovine Hemorrhagic Bowel Syndrome in Belgium and The Netherlands - Bert De Jonge; Bart Pardon; Jeroen Dewulf; Evy Goossens; Jasper het Lam; Evert van Garderen; Stefan Roels; Jozefien Callens; Thierry Petitjean; Koen Chiers (Animals, 2023)
Hemorrhagic bowel syndrome (HBS) is a poorly understood, sporadic and often fatal disease in cattle. Although, HBS is considered an important disease in dairy cattle, epidemiological data is largely lacking. This study describes the epidemiology of HBS in Belgium and the Netherlands, based on necropsy records from 2009 to 2022, and reports characteristics from 27 cows and 35 dairy operations with HBS, gathered through a survey. The annual incidence of HBS has a significantly increasing trend both at cow and herd level, with incidence above 3.2% in necropsied mature dairy cattle in the most recent years. Estimated herd-level incidence in the Netherlands was double the estimated incidence in Belgium, which might be explained by higher herd size in the Netherlands. Occurrence of HBS was most prevalent in fall, being 40.1% higher than the average of the other seasons. In 35 Flemish (Belgian) surveyed dairy herds with HBS, manifestation of HBS was mostly as solitary cases, and if multiple cases occurred, the time interval was highly variable. In addition, the majority of cows with HBS (61.1%; 16/26) were in more than 100 days lactation. In conclusion, HBS is an important and possibly emerging disease in dairy cattle in Belgium and the Netherlands.